HOUT-28. FIRST-LINE TEMOZOLOMIDE VS PCV FOR LOW GRADE GLIOMAS: A 11 YEARS REAL-WORLD DATA FROM CHUM, UNIVERSITY CENTER. (11th November 2019) - Nait Ajjou, Myriam; Assad, Anis; Letourneau Guillon, Laurent; Belanger, Karl; Lemieux Blanchard, Emilie; Lemieux, Bernard; Bahary, Jean-Paul; G Masucci, Laura; Roberge, David; Menard, Cynthia; Lambert, Carole; Moumdjian, Robert; et al.
Abstract: BACKGROUND: Before 2012, Temozolomide (TMZ) was used for low-grade gliomas (LGG) to avoid Lomustine toxicity. After 2012 RTOG data, Procarbazine, Lomustine and Vincristine (PCV) given sequentially with radiotherapy became standard treatment with the side effects burden associated. METHODS: We retrospectively reviewed our SARDO clinical database of patients with low-grade glioma LGG grades 2 and 3 between 2006 and 2017 at CHUM University Health Center. Molecular profile for these tumors is reflex and standard in our institution since 2016. RESULTS: A total of 123 patients were identified with grade 2 and grade 3 LGG; 37 (30%) treated with PCV and 86 (70%) received TMZ. Median follow up was 11mo for PCV 11mo vs 22mo TMZ. Both groups were balanced in terms of median age, sex, neurologic symptoms and surgery rate. 53% patients had tumor untested for IDH1-2 and codeletion1p19q because of diagnostic before 2016. Disparities were noted with a predominance of grade 3 in the TMZ group (74% vs 27%, p< 0.01). TMZ was the preferred regimen before 2012 (100% vs 43%) and PCV became the standard of care after 2012 (0% vs 57%). Radiation use as first line treatment was 90%. The 4y OS was not significantly longer for PCV 50% compared with TMZ 47% with mOS between both groups (PCV NR vs TMZ 39.9mo, p=0.158). When controlled for tumor grade, the 2y OS was 80% for PCV vs 64% for TMZ, p=0.542. The 4y PFS was trendly longer for PCV group 78% than TMZ group 45%, p=0.148. CONCLUSION: As we are still waiting for the prospective ongoing prospective trials comparing these 2 regimens, PCV and radiation are still standard of care regimens for grade 2 and 3 LGG. This retrospective data is not reassuring for a replacement for PCV with TMZ.